Indigenous Tribal Farming for Sustainable Production / (Acc. 3452) - Kella, Lakshmana; Ramaiah, P. V.; Punna Rao, P. (Jodhpur : Agrobios (India), 2007)
With reference to high altitude tribal areas of Andhra Pradesh, India.
Keywords: Traditional farming